2016
DOI: 10.18203/2394-6040.ijcmph20162545
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with caesarean section: a community based cross sectional study in rural parts of Rangareddy district, Telangana, India

Abstract: INTRODUCTIONPregnancy and delivery are generally considered as normal physiological process in women. The type of delivery can be normal, assisted or caesarean section. Caesarean section (CS) is an operative procedure whereby the fetuses after the end of 28 th weeks are delivered through an incision on the abdominal and uterine walls. Rise in incidence of caesarean sections could be due to increased safety of the operation due to improved anesthesia, availability of blood transfusion and antibiotics, other res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…14 Among elective caesarean section in the study of Kumar MV et al most common indication was previous caesarean section, followed by cephalopelvic disproportion. 13 In present study also the main indication for elective CS was previous CS but there is rise in elective Primary CS from 2012 to 2016 and the main indication in 2016 was IUGR with oligohydraminos followed by malpresentation. In a study by Verma et al also the commonest indication for elective cesarean section was previous cesarean section (42%) followed by previous 2LSCS (15%), primi breech (15%), and CPD (14%).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…14 Among elective caesarean section in the study of Kumar MV et al most common indication was previous caesarean section, followed by cephalopelvic disproportion. 13 In present study also the main indication for elective CS was previous CS but there is rise in elective Primary CS from 2012 to 2016 and the main indication in 2016 was IUGR with oligohydraminos followed by malpresentation. In a study by Verma et al also the commonest indication for elective cesarean section was previous cesarean section (42%) followed by previous 2LSCS (15%), primi breech (15%), and CPD (14%).…”
Section: Discussionmentioning
confidence: 46%
“…13 In present study the main indication for emergency Primary CS was fetal distress followed by CPD and then Non progress of labour. Jawa et al also studied that Fetal distress, previous LSCS, NPOL (including failed induction) and Hypertensive disorders of pregnancy (HDP) were the leading indications in the emergency CS.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have confirmed that there is an evident disparity between the two types of health-care services, with greater prevalence of cesarean deliveries in the private sector. 18,[29][30][31] The decision to perform a cesarean section is based primarily on the question of what is best for or may save the lives of the mother and child. The indications for the cesarean section can, therefore, be divided into absolute and relative indications.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a relationship between a concomitant increase in maternal age and caesarian section rate, but they suspected influence by care provider and maternal preferences [25], [26], and increasing parity with maternal age [27]. In India, socio-economic class was related to scarred uterus, the rate thereof reducing with poverty [28]. This factor was not investigated in this study.…”
Section: Discussionmentioning
confidence: 76%
“…In India, socio-economic class was related to scarred uterus, the rate thereof reducing with poverty [28]. This factor was not investigated in this study.…”
Section: Discussionmentioning
confidence: 84%